2018
DOI: 10.1177/0008417418820878
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of robotic arm use on individuals with upper extremity disabilities: A scoping review

Abstract: Background. Robotic arms may help users perform various activities. Even though robotic arms are commercially available, their impacts are still poorly understood. Purpose. This scoping review aimed to identify the potential impacts of using robotic arms for individuals with upper-extremity disabilities and appraise the scientific quality of the selected studies. Method. A search for studies published between 1970 and 2016 was conducted in PubMed, Embase, Compendex, and Scopus. The Canadian Model of Occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Various studies have shown that semiautonomous control models have led to significant improvement in both success rate and execution time of tasks compared with commercially available Cartesian control models. At the same time, in accordance with our results, some studies also show that target groups desire high execution speeds [ 15 , 28 ]. Thus, the user-centered adaptation of movement speed can be interpreted as an essential factor for user experience.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Various studies have shown that semiautonomous control models have led to significant improvement in both success rate and execution time of tasks compared with commercially available Cartesian control models. At the same time, in accordance with our results, some studies also show that target groups desire high execution speeds [ 15 , 28 ]. Thus, the user-centered adaptation of movement speed can be interpreted as an essential factor for user experience.…”
Section: Discussionsupporting
confidence: 92%
“…Reasons for this include technical, economic, and normative challenges and insufficient system implementation potential into existing care processes [ 14 ]. In contrast, there is low level of empirical evidence on the perceived usefulness and acceptance of the systems by the potential user groups [ 15 , 16 ]. The following section provides an overview of the current state of the art.…”
Section: Introductionmentioning
confidence: 99%
“…One type of assistive technology are robotic arms, which are often fixed to an individual’s wheelchair to reach and grasp everyday objects [ 3 5 ]. Powered arm supports are similar, however these devices are attached to the limb and can be controlled to move the individual’s arm to aid in tasks of everyday living [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…JACO and iARM are two of the most popular external robotic arms fixed or mounted on wheelchairs. Both robotic arms were designed to be mounted on a user's motorized wheelchair; they have six degrees of freedom and can reach objects at a distance of 90 cm [5]. A study on the practical demands of the potential users of external robotic arms and upper limb exoskeletons for assistance with ADLs can be found in [6].…”
Section: Introductionmentioning
confidence: 99%